Shear strength characteristics of weathered jointed Kenny Hill interbedded formation for cylindrical specimen under direct shear test - Abbas, Hasan Ali; Mohamed, Zainab; Taher, Muntadher J.; Kudus, Sakhiah Abdul; Ghaltan, Hasanain Muhammad; Salman, Manaf Raid (Zielona Góra: Uniwersytet Zielonogórski)
The sliding failures commonly occur in interbedded formations along the weakness plane of the bedding plane a sedimentary rock or the joint interface. Therefore, studying the shear strength characteristics at the bedding plane or interface is crucial for evaluating the expected failure plane. In this study, the shear strength characteristics of planar jointed Kenny Hill shale, sandstone, and shale-sandstone specimens were investigated using the direct shear box method.
Keywords: shear strength; planner joint; direct shear; weathered sandstone; weathered shale; interbedded